Gaya Kepemimpinan Transformasional, Motivasi Ekstrinsik dan Pengembangan Karir Terhadap Work Performance Karyawan PT Samitex - Nugroho, Irfan Septian; Prayekti, Prayekti; Septyarini , Epsilandri (Politeknik Piksi Ganesha Indonesia, 2024)
The decline in work performance that occurred in this study was generally caused by a decrease in the enthusiasm of co-workers and the absence of examples to use as a reference for achieving work performance. The aim of this research is to examine the influence of transformational leadership, extrinsic motivation and career development on work performance. Research data collection method using questionnaires. The population is employees at PT Samitex Sewon total of 85 people using a saturated sampling technique. Data collection techniques using primary data were analyzed using multiple linear regression, equipped with t test, f test and coefficient of determination. The research results show that there is no influence of transformational leadership on work performance, extrinsic motivation and career development have a positive and significant influence on work performance and the variables of transformational leadership, extrinsic motivation and career development have positive and significant influence on work performance.